Theorizing transformative innovations: the role of agency in real critical junctures - Lilja Mósesdóttir (Edward Elgar Publishing, 2020)
Increased emphasis on the links between regional diversity and regional knowledge, innovation and entrepreneurship highlights the need for a focus on the spatial aspects of these multifaceted, dynamic relationships in order to improve our understanding. By means of a conceptual approach, this timely book illustrates the links between innovation and economic development through the role of space. This thought-provoking book addresses the questions regarding diversity, innovation and clusters that require further investigation and analysis.